Geology and distribution of heavy metals in topsoil, Guchil, Kuala Krai, Kelantan - Renuka A/P Krishnan (2016)
Geological study was carried out approximately 25km² in and around Guchil, Kuala Krai, Kelantan. Based on the field study carried, carbonaceous mudstone interbedded with greywacke sandstone, shale and ignimbrite distribution of rock found in this study. Meanwhile, investigation on distribution and potential heavy metals (Cu, Fe, Mn, Pb and Zn) in topsoil Guchil, Kuala Krai, Kelantan were studied. Soil sample were collected randomly in nine locations in and around Guchil, Kuala Krai, Kelantan. The soil samples undergo soil digestion and the concentration of heavy metals determined via Inductively Coupled Plasma - Optimal Emission Spectroscopy (ICP-OES). The overall heavy metals concentration in the topsoil ranged from 21176-138962; 649-8411; 11-505; 43-455; and 11-115 mg/kg for Fe, Pb, Mn, Zn and Cu respectively. The average concentration of heavy metals in the soil display the following decreasing trend: Fe > Pb > Mn > Zn > Cu. The spatial distribution pattern shows centralized distribution pattern of maximum value of heavy metals in residential area compared to agricultural area by using Interpolation of Inverse Distance Weighed (1DW) method. The concentration of Cu, Fe, Mn, Pb and Zn from the soil samples compared with naturally occurring value of contaminated land management and control guidelines of Department of Environment Malaysia (DOE), 2009 and Barceloux (1999) as well as with permissible limit values in soil of Polish Ministry of the Environment, 2002. From this assessment method, highly potential element is Pb that exceeds the permissible limit value in soil based on land use. The other possible potential heavy metals are Cu and Zn in topsoil.